Criminal Liability of Users of Electronic Advertising Services that are Fraudulent in the Advertising Program of Electronic System Providers - Ilham Giri Wijaya; Gelar Ali Ahmad (NOVUM : JURNAL HUKUM, 2024)
Law enforcement related to advertising fraud in the digital environment faces challenges in regulation, vague interpretation of the ITE Law, and the need for cooperation between the government, system organizers, and consumer awareness. The purpose of this study is to examine and analyze the criminal liability of electronic advertising service users who place fraudulent advertisements on the advertising program of electronic system providers and the legal consequences faced by electronic advertising service users who place fraudulent advertisements on the advertising program of electronic system providers. This research uses normative legal research methods that use statutory and conceptual approaches to answer the problem of criminal liability of electronic advertising service users for fraudulent content on official advertising programs for electronic system providers. Primary legal materials used include laws and regulations related to electronic systems and secondary legal materials in the form of legal literature and scientific journals. Analysis of legal materials is carried out descriptively prescriptively to find answers to the problems raised. The results show that in the context of using online advertising services in Indonesia, the installation of fraudulent advertisements on the advertising program of electronic system providers has the potential to face criminal sanctions such as prosecution, fines, or imprisonment, in accordance with the ITE Law, Criminal Code, Consumer Protection Law, and Broadcasting Law. Individuals and corporations involved in this practice may also face administrative sanctions, revocation of business licenses, and civil lawsuits. These serious legal consequences can include significant financial penalties and serious reputational damage, in addition to possible revocation of operating licenses as electronic system operators. Both subjects may face serious legal implications for harming consumers and violating applicable electronic advertising laws.